2023
DOI: 10.1177/17562864231156674
|View full text |Cite
|
Sign up to set email alerts
|

Microglia as a cellular target of diclofenac therapy in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is an untreatable cause of dementia, and new therapeutic approaches are urgently needed. AD pathology is defined by extracellular amyloid plaques and intracellular neurofibrillary tangles. Research of the past decades has suggested that neuroinflammation plays a critical role in the pathophysiology of AD. This has led to the idea that anti-inflammatory treatments might be beneficial. Early studies investigated non-steroidal anti-inflammatory drugs (NSAIDS) such as indomethacin, celecox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 122 publications
(221 reference statements)
0
5
0
Order By: Relevance
“…Aside from their effects on AChE, AChEIs possess other biological activities, including suppression of Aβ plaque formation and brain inflammation [ 61 64 ]. Moreover, in this study we chose donepezil as anti-inflammatory control, rather than other typical medicines, such as Ibuprofen, mainly because the data regarding treatment of AD with Ibuprofen from epidemiological studies, clinical trials and meta-analyses in the past is still controversial [ 65 ]. Interestingly, several in vitro and in vivo studies have reported the anti-inflammatory effects of donepezil on various stimulus-induced inflammatory responses [ 66 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from their effects on AChE, AChEIs possess other biological activities, including suppression of Aβ plaque formation and brain inflammation [ 61 64 ]. Moreover, in this study we chose donepezil as anti-inflammatory control, rather than other typical medicines, such as Ibuprofen, mainly because the data regarding treatment of AD with Ibuprofen from epidemiological studies, clinical trials and meta-analyses in the past is still controversial [ 65 ]. Interestingly, several in vitro and in vivo studies have reported the anti-inflammatory effects of donepezil on various stimulus-induced inflammatory responses [ 66 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid deposits activate microglia, which then release neurotoxins; amyloid also stimulates an overall immune response [41]. For AD treatment, many nonsteroidal antiinflammatory agents (NSAIDs) have been used with highly variable responses [41,42]. Diclofenac is the only NSAID associated with a significant reduction in cognition.…”
Section: Treatment To Reverse Neuroinflammationmentioning
confidence: 99%
“…Diclofenac is the only NSAID associated with a significant reduction in cognition. A report of a retrospective cohort study of 1431 patients with AD receiving diclofenac showed a reduced incidence of dementia as compared to other NSAIDs; that report discussed the mechanisms whereby diclofenac is effective [42].…”
Section: Treatment To Reverse Neuroinflammationmentioning
confidence: 99%
“…As in other neurological disorders, the first class of drugs tested in the neuroinflammatory pathway was the non-steroidal anti-inflammatory drugs (NSAIDs) [ 171 ]. NSAIDs were proposed due to the generalized anti-inflammatory effect aiming to suppress activated microglia.…”
Section: Beyond Amyloid: Tau and Neuroinflammationmentioning
confidence: 99%